ChemInform Abstract: Multidirectional Synthesis of Substituted Indazoles via Iridium‐Catalyzed C—H Borylation. Issue 40 (October 2015) - Sadler, Scott A.; Hones, Andrew C.; Roberts, Bryan; Blakemore, David; Marder, Todd B.; Steel, Patrick G.
Abstract In the absence of any steric directing group, the title reaction proceeds selectively at C‐3 of the indazole skeleton.